The Impact of Institutions on Multidimensional Poverty Reduction in Vietnam - Loi, Ngo Thang; Huong, Vu Thanh; Duc, Do Anh; Dung, Ngo Quoc; Van, Vu Quynh (Journal of Social Economics Research, 2022)
For many years, poverty has been a problem in many developing countries in general and in Vietnam in particular. Studies assessing the impact of institutions on multidimensional poverty have only been applied in Vietnam since 2016. The purpose of this study is to evaluate the impact of institutions on multidimensional poverty reduction in Vietnam using multilevel data at household and provincial levels in Vietnam. Institution is calculated from a survey of people's perceptions on three aspects (performance, quality of policy implementation, and service delivery by local governments) from 63 provinces and cities in Vietnam to advocate for effective and responsive governance. The results assert the positive impact of institutional efficiency on reducing multidimensional poverty using multilevel Probit models. The study also indicates that the impact of institutions on multidimensional poverty is different among localities, and for urban and high-income localities the institutions have a reverse impact.